The Implementation Of SAK ETAP In Finenacial Reports Presentation At The Notary Office Of Angga Prisma Jelita, S.H., M.Kn In Bengkulu City - Neri Susanti; Kamelia Astuti; Deta Alvionita (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
This study aims to implement SAK ETAP in the presentation of financial reports and to find out the financial condition after the implementation of SAK ETAP. Research at the Notary Office of Angga Prisma Jelita, S.H., M.Kn in Bengkulu City is a type of comparative descriptive research, to collect and compile data, data collection methods are needed, namely interviews and documentation. The results of research at the Notary Office of Angga Prisma Jelita, S.H.M.Kn Bengkulu City, the financial reports presented are not in accordance with SAK ETAP. Notary Office of Angga Prisma Jelita, S.H., M.Kn in Bengkulu City does not make financial reports, balance sheets, profit and loss and notes to its financial reports. Therefore, researchers have implemented financial reports at the Notary Office of Angga Prisma Jelita, S.H., M.Kn in Bengkulu City in accordance with the Financial Accounting Standards for Entities Without Public Accountability.